2015
DOI: 10.1007/s11692-015-9324-9
|View full text |Cite
|
Sign up to set email alerts
|

Head, Body and Fins: Patterns of Morphological Integration and Modularity in Fishes

Abstract: Actinopterygians demonstrate high levels of morphological disparity, especially in the variation of fin positions, sizes and shapes. One hypothesis to explain the diversity of fin morphologies is that it is facilitated by a modular organization. According to this hypothesis, fin modules would be quasi-independent during ontogeny or evolution, facilitating their evolvability. We investigated variational modularity of fins in two cyprinid species, the zebrafish (Danio rerio) and the Northern redbelly dace (Chros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 80 publications
4
25
0
Order By: Relevance
“…A patterning module was also hypothesized for the caudal fin [219]. In contrast, in a recent study focusing on variational modularity in two cyprinid species, we showed good support for the hypothesis that the dorsal, anal, and caudal fins formed one variational module including the caudal peduncle, while the paired fins formed another variational module [222]. Because modularity is a hierarchical concept, a hypothesis of evolutionary modularity worth investigating is that the median fin system as a whole could constitute one module, the paired fin system could constitute a second independent module, and the dorsal and anal fins could constitute a third module nested within the median fins module (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…A patterning module was also hypothesized for the caudal fin [219]. In contrast, in a recent study focusing on variational modularity in two cyprinid species, we showed good support for the hypothesis that the dorsal, anal, and caudal fins formed one variational module including the caudal peduncle, while the paired fins formed another variational module [222]. Because modularity is a hierarchical concept, a hypothesis of evolutionary modularity worth investigating is that the median fin system as a whole could constitute one module, the paired fin system could constitute a second independent module, and the dorsal and anal fins could constitute a third module nested within the median fins module (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…For instance, pectoral fin shape in many fishes determines swimming speeds (Bellwood & Wainwright, ; Fulton, Bellwood, & Wainwright, ; Wainwright, Bellwood, & Westneat, ). Pectoral fin shape is also evolutionarily correlated with a number of other external phenotypes that could be adaptive (Feilich, ; Larouche, Cloutier, & Zelditch, ). Critically, in both Malawi and Tanganyikan cichlids, larger pectoral fin muscles and fin areas are correlated and are convergently associated with feeding from the substrate as opposed to feeding in the water column (Colombo, Indermaur, Meyer, & Salzburger, ; Hulsey et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of resource allocation trade‐offs have suggested tissue proximity to be a potential predictor of changes in investment (Emlen, ). Although organisms must use a finite energy budget to accumulate body mass, the ubiquity of modularity in organismal systems ranging from mammals to fishes (Esteve‐Altava, ; Larouche, Cloutier, & Zelditch, ) without obvious trade‐offs between adjacent tissues (reviewed in Warren & Iglesias, ) suggests that simple economic predictions between morphological modules may not have much explanatory power for understanding the evolution of most ontogenetic pathways without a more detailed perspective of lineage‐specific energy budgets and life history. While investment trade‐offs between morphological modules have provided evidence for the expectations of the ETH in a few animal lineages (Emlen, ; Liao et al., ; Moczek & Nijhout, ), the large number of studies that have failed to recover support in other lineages suggests that the broad expectations of the ETH are far from a universal rule (reviewed in Warren & Iglesias, ).…”
Section: Discussionmentioning
confidence: 99%